Investigation of Electrochemical and Thermal Properties of Ti50Ni40-xZr10Nbx SMAs - Abdullah, Shakhawan Salih; Balci, Esra; Qader, Ibrahim Nazem; Dagdelen, Fethi (Springer, 2025)
Titanium and its alloys have already been widely used as implant materials due to their outstanding mechanical characteristics, thermal properties, and biocompatibility. In this study, Ti50Ni40-xZr10Nbx (x = 1, 3, 5 at.%) shape memory alloys (SMAs) with a constant atomic percentage of Ti and Zr were investigated. For investigation of the structural properties of produced SMAs, scanning electron microscope (SEM-EDX) analysis, optical microscope (OM) images, and x-ray diffraction (XRD) pattern were taken. B2, B19', beta-Nb, and Ti2N phases were detected in all alloys. In SEM-EDX and OM research, it was determined that beta-Nb phase increased in dendritic structure as the Nb ratio increased. For the biocompatibility levels of alloys, the corrosion test method was carried out with the potentiodynamic test, which is one of the electrochemical methods. Tafel test and electrochemical impedance spectroscopy in a simulated body fluid (SBF) showed that the Nb additive increased the corrosion resistance of the alloy. Phase transformation temperatures (PTTs) of these alloys were investigated by using differential scanning calorimetry (DSC) measurements. In DSC research, it was determined that the alloys have a shape memory effect (SME), and the PPTs of the alloys decreased as the Nb ratio increased.
Keywords: biocompatibility; NiTiZrNb; potentiodynamic test; shape memory alloy